Women's Participation in the Digital Economy Universally and Locally: Reality and Challenges - علي , راما; مدى شريقي (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The study aimed to identify the reality of women's participation in the digital economy and determine the extent of the compatibility between women's education and the requirements of the new digital economy, and the challenges that face their effective participation. The current study relied on the analytical descriptive approach. The study found a series of results, the most important of which are: widening of the digital gender gap in the digital economy through the low participation rate of women in technological jobs. In addition, women continue to perform traditional jobs that they have always worked at, such as administrative work, marketing, e-commerce, and education. Arab countries, including Syria, also suffer from a widening digital gap, with female graduates excelling in scientific disciplines related to the development of the digital economy, in exchange for low participation in the digital labor market. In light of the results, the study made several recommendations: the importance of creating an infrastructure to improve women's digital skills, taking into account the low levels of formal education in poor countries, and developing women's skills in businesses that are less exposed to the risks of automation.